A problem-based learning resource in emergency medicine for medical students. Issue 5 (1st September 2000) - Kelly, Anne-Maree
Abstract : Emergency medicine is a relatively new specialty area within medicine, however medical schools, students and standard setting bodies have recognised that learning emergency medicine is integral to the training of medical students. There are, however, significant problems with the delivery of emergency medicine teaching including low teacher numbers, severely limited teaching time and lack of suitable learning resources. This paper describes the process of development of a learning resource, its format and content and summarises student feedback.